Some measurements of the conductivities of dilute potassium chloride solutions - Faure, Abraham (Rhodes University, Faculty of Science, Department of Chemistry, 1954)
A constant temperature room has been constructed in which the thermoregulator is controlled by a temperature-sensitive resistance. A thermostat has been constructed in which the 0 temperature is controlled to within 0.001Â°C. A precision conductance bridge has been built in a very convenient form. Improvements include the replacement of the telephone as null detector by a cathode ray oscilloscope, and the use of a resistance-capacity phase-shift oscillator, which gives a good wave-form. An automatic recycling conductance water still has been built which regularly gives water with a conductivity less than 0.09 micromhos per cm. The conductivities of dilute KCl solutions have been measured, taking special care to prevent errors due to the adsorption of KCl on the surface of glass. Two cells were used for these measurements : a modified Jones cell, and a special conductimetric titration cell. The modified Jones cell has given results in good agreement with the generally-accepted values. The results of the conductimetric titration cell do not agree well with the generally-accepted values; the greatest difference (for the most dilute solution) is 0.4%. The reason for this is not known.
Keywords: Potassium chloride